PENERAPAN PERSONNEL DAN CULTURAL CONTROL BERBASIS NILAI KRISTIANI TERHADAP KUALITAS LAYANAN DI KLINIK KECANTIKAN Dr. WIT SURABAYA - Martha Ayu Monica; Wiyono Pontjoharyo (Perpustakaan Universitas Surabaya, 2018)
e recent adoption of informal procedures is a very interesting review, especially for working conditions where the organization is not focused on profit, so the organization strives to pay attention to the satisfaction of existing staff work by building on existing controls, thereby affecting staff performance that will ultimately affect the quality of existing services. The application of Christian values to improve employee performance is one of the methods used by business entities. Therefore, management should be able to build a strong organizational culture and apply appropriate control system design. This study aims to find out about how the application of personnel and cultural control based on Christian values on service quality and customer satisfaction in clinic beauty. Wit. Therefore, the object of research used is Dr. Wit beauty clinic. During the study, various data used were obtained from various methods, such as interviews, observation, document analysis, and literature study. The results showed that basically the quality of service in a business entity that can be met if the personnel and culture control that is applied well. This study also discusses how the application of Christian values in the personnel and cultural control and provides some improvement or recommendation on the weakness of personnel and cultural control in improving the quality of services that can be considered by the owner of Dr. Wit beauty clinic.